2020
DOI: 10.1021/acs.biochem.0c00261
|View full text |Cite
|
Sign up to set email alerts
|

The Heme–Lys Cross-Link in Cytochrome P460 Promotes Catalysis by Enforcing Secondary Coordination Sphere Architecture

Abstract: Cytochrome (cyt) P460 is a c-type monoheme enzyme found in ammonia-oxidizing bacteria (AOB) and methanotrophs; additionally, genes encoding it have been found in some pathogenic bacteria. Cyt P460 is defined by a unique post-translational modification to the heme macrocycle, where a lysine (Lys) residue covalently attaches to the 13′ meso carbon of the porphyrin, modifying this heme macrocycle into the enzyme’s eponymous P460 cofactor, similar to the cofactor found in the enzyme hydroxylamine oxidoreductase. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…The NPs are active for NO binding in the ferric oxidation state (in contrast to H-NOX type NO sensors, which are active in the ferrous state), and use the corresponding ls-{FeNO} 6 adduct for NO transport and delivery. The highly ruffled hemes of rNPs are thought to prevent autoreduction of the ls-{FeNO} 6 complex. The autoreduction reaction of ferric heme-nitrosyls is observed for globins, for example, and small-molecule model systems, and proceeds by addition of base to the electrophilic NO + ligand in ls-{FeNO} 6 adducts (due to their Fe­(II)–NO + electronic structures; see Section ): where eq is the inverse of the nitrite reduction reaction in eq .…”
Section: Introductionmentioning
confidence: 99%
“…The NPs are active for NO binding in the ferric oxidation state (in contrast to H-NOX type NO sensors, which are active in the ferrous state), and use the corresponding ls-{FeNO} 6 adduct for NO transport and delivery. The highly ruffled hemes of rNPs are thought to prevent autoreduction of the ls-{FeNO} 6 complex. The autoreduction reaction of ferric heme-nitrosyls is observed for globins, for example, and small-molecule model systems, and proceeds by addition of base to the electrophilic NO + ligand in ls-{FeNO} 6 adducts (due to their Fe­(II)–NO + electronic structures; see Section ): where eq is the inverse of the nitrite reduction reaction in eq .…”
Section: Introductionmentioning
confidence: 99%
“…These similar frequencies suggest that the CLD pro-enzyme remains ruffled, in accord with the structural data obtained for CLD Lys106Leu/Ala131Glu N. sp AL212 cyt P460. (10) Characterization by X-band EPR at 12 K showed that protein is a mixture of S = 5 /2 signals that were consistent with a cross-link containing and a CLD cyt P460 (Fig. 2b).…”
Section: Anaerobic Overexpression Yields Cross-link Deficient Cyt P460 Pro-enzymementioning
confidence: 89%
“…Complementary investigations of cyt P460 variants with substituted residues in their distal pockets, combined with a 2.25 Å structure of a cross-link deficient (CLD) cyt P460 variant strongly suggest that the role of the heme-Lys cross-link is to position the cofactor at a sufficiently close distance to a carboxylate group to enable proton transfer during the initial step(s) of NH2OH oxidation. (10,11) While a clear picture is emerging of the functional role of the heme-Lys cross-link, its origins have remained mysterious. The apparent non-necessity of molecular chaperones in recombinant expression of functional, cross-linked cyt P460 has led to speculation that the heme-Lys PTM forms via an autocatalytic process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxylamine oxidizing cytochrome P460 has a unique lysine crosslinked c -type monoheme. 68 This heme–Lys crosslink plays a role as a mechanical restraint to bring the secondary sphere glutamate residue close enough to promote catalysis. A hemoglobin, GlbN-A from cyanobacterium Synechococcus , is capable of showing ˙NO dioxygenase activity and has an unusual heme–His crosslink installed by protein posttranslational modification.…”
Section: Discussionmentioning
confidence: 99%